Experimental and Numerical Modeling of a Sloshing Problem in a Stepped Based Rectangular Tank - Cruchaga-Ssa., M; Castillo-Del Barrio, E; Gandara-Imilqueo, T (American Institute of Physics, 2021)
In this study, the two-dimensional sloshing of water in a stepped based tank partially filled was analyzed using an arbitrary Lagrangian-Eulerian adaptive fixed-mesh method and including the Smagorinsky turbulence model. The numerical model is verified by contrasting the predictions made by the model with experimental results. The tank was subjected to controlled one-directional motion imposed using a shake table. The free surface evolution was followed using ultrasonic sensors, and a high-speed camera was used to record the experiments. The experimental and numerical analyses include a comparison of the wave height at different control points and snapshots of the free surface evolution for two imposed frequencies. Also, a detailed numerical study of the effects of the frequency of the imposed movement, the step height, and the fluid volume on the wave dynamics was performed. Moreover, the effect of fluid viscosity on the dynamics of the free surface was also studied. In brief, the numerical method proved to be accurate, experimental data were reported, and the effects on the numerical results of different physical and numerical aspects were exhaustively analyzed. The proposed results help to understand the sloshing of stepped geometries. © 2021 Author(s).